Use of deep eutectic solvents in environmentallyfriendly dye-sensitized solar cells and their physicochemical properties: a brief review - Pishro, Khatereh [Unesp] (2024)
A novel way to mitigate the greenhouse effect is to use dye-sensitized solar cells (DSSCs) to convert carbon dioxide from the air into useful products, such as hydrocarbons, which can also store energy from the sun, a plentiful, clean, and safe resource. The conversion of CO2 can help reduce the impacts of greenhouse gas emissions that contribute to global warming. However, there is a major obstacle in using DSSCs, since many solar devices operate with organic electrolytes, producing pollutants including toxic substances. Therefore, a key research area is to find new eco-friendly electrolytes that can effectively dissolve carbon dioxide. One option is to use deep eutectic solvents (DESs), which are potential substitutes for ionic liquids (ILs) and have similar advantages, such as being customizable, economical, and environmentally friendly. DESs are composed of low-cost materials and have very low toxicity and high biodegradability, making them suitable for use as electrolytes in DSSCs, within the framework of green chemistry. The purpose of this brief review is to explore the existing knowledge about how CO2 dissolves in DESs and how these solvents can be used as electrolytes in solar devices, especially in DSSCs. The physical and chemical properties of the DESs are described, and areas are suggested where further research should be focused.